Impact of BRAFV600E mutation on aggressiveness and outcomes in adult clonal histiocytosis - Razanamahery, Jerome; Godot, Amelie; Leguy-Seguin, Vanessa; Samson, M.; Audia, Sylvain; Bonnotte, Bernard (Frontiers in Immunology, 2023)
Histiocytoses encompass a wide spectrum of diseases, all characterized by tissue infiltration by CD68+ histiocytes. Most adult histiocytoses are considered clonal diseases because they highlight recurrent somatic mutations in the MAP-kinase pathway gene, primarily BRAF. The presence of BRAF mutation is associated with widespread disease in children with Langerhans cell histiocytosis (LCH) or cardiovascular/neurological involvement in Erdheim–Chester disease (ECD). Nevertheless, few data are available on adult clonal histiocytosis. This is why we have conducted a retrospective study of all patients with clonal histiocytosis in our institution and present the data according to the presence of BRAF mutation. Among 27 adult patients (10 ECD, 10 LCH, 5 Rosai–Dorfman disease (RDD), and 3 mixed ECD/LCH), 11 (39%) have BRAF mutation with gain of function (n = 9) and deletion (n = 2). Those patients had frequent multicentric disease with risk organ involvement, especially the brain and cardiovascular system. They had frequent associated myeloid neoplasms (mostly chronic myelomonocytic leukemia) and received more frequently targeted therapy as the front-line therapy. Nevertheless, its presence did not affect the overall survival or relapse-free survival probably due to the emergence of efficient therapies. To conclude, rapid and accurate molecular establishment in adult clonal histiocytoses is crucial because BRAFV600E mutation correlates with multicentric disease with organ involvement and incomplete metabolic response.